Antenna proton sensitivity determines photosynthetic light harvesting strategy. (28th June 2018) - Kuthanová Trsková, Eliška; Belgio, Erica; Yeates, Anna M; Sobotka, Roman; Ruban, Alexander V; Kaňa, Radek
Abstract : The extent of proton sensitivity in antenna proteins determines the photosynthetic light harvesting strategy in plants and algae. Abstract: Photoprotective non-photochemical quenching (NPQ) represents an effective way to dissipate the light energy absorbed in excess by most phototrophs. It is often claimed that NPQ formation/relaxation kinetics are determined by xanthophyll composition. We, however, found that, for the alveolate alga Chromera velia, this is not the case. In the present paper, we investigated the reasons for the constitutive high rate of quenching displayed by the alga by comparing its light harvesting strategies with those of a model phototroph, the land plant Spinacia oleracea . Experimental results and in silico studies support the idea that fast quenching is due not to xanthophylls, but to intrinsic properties of the Chromera light harvesting complex (CLH) protein, related to amino acid composition and protein folding. The p K a for CLH quenching was shifted by 0.5 units to a higher pH compared with higher plant antennas (light harvesting complex II; LHCII). We conclude that, whilst higher plant LHCIIs are better suited for light harvesting, CLHs are 'natural quenchers' ready to switch into a dissipative state. We propose that organisms with antenna proteins intrinsically more sensitive to protons, such as C. velia, carry a relatively high concentration of violaxanthin to improve their light harvesting. In contrast, higher plants need less violaxanthin per chlorophyll because LHCII proteins are more efficient light harvesters and instead require co-factors such as zeaxanthin and PsbS to accelerate and enhance quenching.